A Neogene Heritage: Conifer Distributions and Endemism in Mediterranean-Climate Ecosystems - Rundel, Philip W. (Frontiers in Ecology and Evolution, 2019)
2The five mediterranean-type climate (MTC) regions of the world, notable for their globally significant levels vascular plant diversity and endemism, fall into two groups. The Cape Region of South Africa and southwestern Australia are ancient and relatively climatically and tectonically stable landscapes with very high species richness relative to their area. This richness reflects a core of paleoendemic lineages as well as Neogene diversification. In contrast, California, the Mediterranean Basin, and central Chile are young climatically and tectonically dynamic landscapes that have developed significant floras in the Neogene. This relative pattern of species richness breaks down when only conifers are considered. Collectively the five MTC regions have a conifer flora of 122 species, almost 20% of the global total, and are rich in endemic conifers species. This diversity is heavily centered in California with 58 species (31 endemic) and the Mediterranean Basin with 40 species (32 endemic). The key to success of conifers in the Northern Hemisphere MTC regions has been the evolution of functional hydraulic traits associated with cold and/or drought tolerance, as exemplified by Neogene diversification in many clades of Pinaceae and Cupressaceae, and by ecophysiological traits that offer competitive advantages over angiosperms on oligotrophic soils. Podocarpaceae and many other Southern Hemisphere conifer lineages never developed equivalent traits and were poorly adapted to surviving increasingly cool and strongly seasonal climate regimes with associated aridity in the late Neogene. Because of extinctions, conifer lineages in the Southern Hemisphere today exhibit a significantly older distribution of divergence ages than their counterparts in the Northern Hemisphere and are home to many isolated relict taxa. This can be seen well in Chile and the Cape Region where there has been little or no Neogene diversification of conifers and a preponderance of relict Gondwanan lineages remain. Only Callitris in southwestern Australia among the Southern Hemisphere MTC floras has been able to evolve successful ecophysiological traits to adapt to aridity in a fire-prone environment and diversify. Traits of cold, drought, and low nutrient tolerance of Northern Hemisphere conifers, most notably in the Pinaceae, have led to their widespread introduction in Southern Hemisphere agroforestry